Improving the quality of work team training by adopting Six Sigma technology: a case study in Yarmouk Educational Hospital - Ghani Dahham Al-Zubaidi; Hussein Walid Hussein (Iraqi Journal for Administrative Sciences, 2025)
The research dealt with the possibility of employing technique of Six sigma to improve the quality of training teams work , and that by identifying problems that may face the process of training teams at all stages , the sample have included (5) teams comprised of (28) members of the staff in Al-Yarmouk teaching hospital , the checklist has adopted to explore the views of respondents to the questions asked , as the researchers fill the list in light of the research stipulates " the Six sigma technique contributes to improving the quality of training teams " the appropriate number of statistical methods has been used to data analysis . the most important outcome of the research show that the use of it Six sigma can help improve the training teams work , and therefore find recommended to take advantage of the importance of Six sigma technique in improving training teams in the organization surveyed.